2010
DOI: 10.4314/gjedr.v8i1-2.53769
|View full text |Cite
|
Sign up to set email alerts
|

The television factor in vocabulary development among secondary school students in Cross River state, Nigeria

Abstract: This study investigated the influence of television viewing frequency on the performance in vocabulary development of SS 3 students in Cross River State, Nigeria. Data were obtained through questionnaires and a vocabulary test administered to 993 students in selected public and private schools in Cross River State. Data analyses indicated that high frequency television viewers performed significantly better than moderate viewers, while moderate viewers performed significantly better than did the low frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…6, No. 2;2013 twice in order to understand it. Meanwhile, 73.7 % of them write a message or sms in English.…”
Section: 4mentioning
confidence: 99%
See 2 more Smart Citations
“…6, No. 2;2013 twice in order to understand it. Meanwhile, 73.7 % of them write a message or sms in English.…”
Section: 4mentioning
confidence: 99%
“…This is in line with the findings made by Asgari and Mustapha (2011) who reported that this strategy was also the most frequently chosen cognitive strategy among the English second language learners in their study. In earlier study, Omojuwa et al (2010) had pointed that the second language learners can develop their vocabulary from watching English Language TV shows. Thus, it seems television as a media still has impact on second language learning.…”
Section: Cognitive Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…These low-language ratings are due more to the quality of the show than to the time spent watching TV programmes. Omojuwa et al (2009) argued that programs for the general public are not intended for teaching purposes, but for entertainment purposes. These include soaps, movies, entertainment, documentaries, musicals, sports (football games), television reality shows, comedy talk shows, cartoons etc.…”
Section: Introductionmentioning
confidence: 99%